Prevalence of MRSA in Rawal Institute of Health Sciences Islamabad & its Antibiotic Susceptibility Pattern - Naila Hina Qazi, Muhammad Alam , Beenish Batool Alam , Jehan Ara , Nadira Sultana , Naila Hina Qazi, Muhammad Alam , Beenish Batool Alam , Jehan Ara , Nadira Sultana (Journal of Rawalpindi Medical College, 2020)
Objective: To determine the prevalence of MRSA infection and its antibiotic susceptibility pattern in patients undergoing abdominal and vaginal surgeries. Material and Method: A retrospective observational study was conducted at Rawal General & Dental Hospital, Islamabad from September 2017 to September 2018 and data of approximately 300 patients were retrieved which included culture and sensitivity reports of wound and vaginal swabs of patients undergoing abdominal and vaginal surgeries to see prevalence of MRSA and antibiotics to which it is susceptible .Obesity was a risk factor and patients with immune-compromised status were not included. Result: Female patients were most affected 87%. Of the total cases, patients between ages 21 to 30 years were more frequent. The rate of MRSA was 37.0% in this study. There were 63% patients who showed methecilline resistance. Linezolid was more effective in MRSA and was sensitive in 81%.